Women as Environmental Protectors: A Case Study on Cross-Generational Stewardship in Hunza - Mehwish Murtaza; Abida Sharif; Seema Shah (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
Environmental protection has become a global concern, requiring collective action and innovative solutions. Women are increasingly recognized for their contributions to environmental sustainability. A qualitative research design was implemented, focusing on a family unit as the case study. A total of 16 participants, eight from the younger generation and eight from the elder generation, were involved in in-depth interviews using a purposive sampling technique. The Objectives of the study are to explore the awareness and knowledge of environmental protection, explore their household management in environmental protection, examine their communal activities to save the environment, and explore the transmission across generations. Thematic analysis was conducted, revealing that elderly women often lack awareness and knowledge regarding environmental issues. However, their traditional practices significantly contribute to environmental protection. On the other hand, some of these practices, due to the lack of awareness and resources, have also had negative impacts on the environment. Younger individuals generally have a better understanding of environmental protection. However, reliance on technology has also led to practices that contribute to pollution. Beyond household efforts, women play an active role in community events, participate in local organizations, and lead workshops and awareness campaigns focused on protecting the environment. Environmental knowledge is passed down through generations, creating a reciprocal exchange through storytelling, experiences, and formal education. This study highlights the significant contributions of women to environmental protection. Policymakers should create specific policies that support and enhance the role of women in environmental management. Additionally, it is recommended to conduct more quantitative research to better understand the knowledge and practices of women in environmental protection and to further emphasize their critical contributions.